Penggunaan Teknik Kuantitatif Di Kalangan Pentadbir Politeknik Kementerian Pendidikan Malaysia - Zulkifli, Ani (2001)
The purpose of this study was to examine the status and extent to which administrators of polytechnics of the Ministry of Education Malaysia apply quantitative techniques of management in planning, directing, reporting and controlling activities for enhancing their administrative and academic decision-making capability. The study followed guidelines of exploratory and descriptive research. Data were collected through a questionnaire mailed to the target administrators. Data were analysed using descriptive statistics to describe administrators' decision-making capability in terms of the extent of utilisation of the selected techniques. Based upon a 74 percent response rate, the findings show that administrators have moderate knowledge about the techniques and their extent of use is fairly low. The most related techniques related to familiarity and extent of use were Statistics, Benchmarking and TQM. Respondents showed positive perception regarding the use and benefits of quantitative techniques. Lack of competence personnel and freedom to make decision were frequently stated. Based upon these findings, practical implications are discussed and suggestions for future research are made.